2016
DOI: 10.3171/2016.1.spine151156
|View full text |Cite
|
Sign up to set email alerts
|

Combined surgical and endovascular treatment of complex high-flow conus medullaris arteriovenous fistula associated with Parkes Weber syndrome: case report

Abstract: Parkes Weber syndrome (PWS) is a congenital overgrowth disorder characterized by unilateral limb and axial hypertrophy, capillary malformations of the skin, and high-flow arteriovenous fistulas (AVFs). Spinal AVFs in the setting of PWS are challenging vascular lesions that often contain multiple arteriovenous (AV) shunts. The present case report highlights an adolescent girl with PWS who presented with a ruptured complex high-flow conus medullaris AVF. She was successfully treated with endovascular emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To our current knowledge, treating methods of AVMs are basing on 3 types [8][9][10][11][12], Arterial Embolization (AE), interventional management and surgical treatment. Previous studies have shown that the potential for the embolization treatment of recanalization of AVMs in other areas, then the follow-up visits confirmed the effective results [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…To our current knowledge, treating methods of AVMs are basing on 3 types [8][9][10][11][12], Arterial Embolization (AE), interventional management and surgical treatment. Previous studies have shown that the potential for the embolization treatment of recanalization of AVMs in other areas, then the follow-up visits confirmed the effective results [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, open vascular interventions won’t be optimal in such situations [ 15 ]. Another option is the combination of endovascular and open vascular interventions, which would help in ensuring complete resection and occlusion [ 1 , 9 ]. Sometimes it is also required to undergo both endovascular and open vascular interventions at multiple stages [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is always challenging to treat SDAFs, especially the complex multichannel connections between arteries and veins without an intervening capillary bed. The high arterial blood flow pooling into the veins may cause hemorrhage, or vessels may grow and cause a mass effect compressing the spinal cord, spinal canal, and bone remodeling and widening due to long-standing pulsatile effects [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent literature reviews [ 8 , 12 ], there were reports of only a handful of thoracolumbar AVFs that manifested purely with cranial SAH. Most of these were correctly diagnosed before the onset of neurological deterioration [ 13 , 14 , 15 , 16 ]. A few instances resembled the case presented herein in that the correct diagnosis was revealed only after a second hemorrhage and clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%